2019
DOI: 10.1016/j.appdev.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Differences in boys' and girls' attachment to pets in early-mid adolescence

Abstract: The precise nature of attachment to pets and differences between girls' and boys' relationships at age 11, 13 and 15 years are investigated in this paper. Data from the 2010 Health Behaviour in School-aged Children (HBSC) survey in Scotland were used to examine qualities of adolescents' attachments to their pet dogs, cats and small mammals. Survey participants (N=2,472) answered pet ownership questions and completed the 'Short Attachment to Pets Scale' (SAPS). Multivariate analysis revealed main effects of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 62 publications
8
35
1
Order By: Relevance
“…Gender differences in dog care reflect the results of previous empirical research [37] in which female students were found to be more attached to pets than males. According to some researchers, modern human attachment behaviour, affection, and caregiving are more developed and stronger in women than in men, and maternal characteristics have been extended from babies to family dogs [39].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Gender differences in dog care reflect the results of previous empirical research [37] in which female students were found to be more attached to pets than males. According to some researchers, modern human attachment behaviour, affection, and caregiving are more developed and stronger in women than in men, and maternal characteristics have been extended from babies to family dogs [39].…”
Section: Discussionsupporting
confidence: 78%
“…Research has shown that children who care for pets themselves feel more connected to them than children that share the responsibility for a pet with other family members [32]. Muldoon, Williams, and Currie [37] studied types of attachment to pets in groups of eleven-, thirteen-, and fifteen-year-olds. They found a pattern of decreasing attachment to pets with age.…”
Section: Children and Petsmentioning
confidence: 99%
“…More specifically, past research shows that girls often score higher than boys on emotional language (Bryant, 1992;Maftei & Holman, 2019;Muldoon, Williams, & Lawrence, 2015;Muldoon, Williams, & Currie, 2019;Tardif-Williams & Bosacki, 2017), and engage in more comforting behaviors and adopt sad or understanding expressions when they observe another's discomfort or unease (Connellan, Baron-Cohen, Wheelwright, Batki, & Ahluwalia, 2000;Hoffman, 1977). However, contrary evidence for gender differences has been found in children's perceptions of peer and companion animal friendships.…”
Section: The Present Studymentioning
confidence: 99%
“…Research to date on children's developing social cognitive skills, including Theory of Mind, has focused largely on the interconnections among children's understanding of other people's thoughts and emotions (Hughes, White, & Ensor, 2014). However, past research has largely overlooked how children's engagement with companion animals may influence their theory of mind development (and vice versa), as studies on children's experiences with companion animals are often marginalized in the field of human-animal interaction studies (Muldoon, Williams, & Currie, 2019;Tipper, 2011). For example, theory of mind research may help to explain why companion animals are commonly perceived to have higher cognitive and emotional capacities than other animals (Cassels, et al 2017).…”
Section: Mental State Talk and Children's Friendshipsmentioning
confidence: 99%
See 1 more Smart Citation